2017
DOI: 10.3390/electronics6010023
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of a Magnetically Dead Layer on the Surface of an Anatase (Ti,Co)O2 Thin Film via an Ultrathin TiO2 Capping Layer

Abstract: Abstract:The effect of an ultrathin TiO 2 capping layer on an anatase Ti 0.95 Co 0.05 O 2−δ (001) epitaxial thin film on magnetism at 300 K was investigated. Films with a capping layer showed increased magnetization mainly caused by enhanced out-of-plane magnetization. In addition, the ultrathin capping layer was useful in prolonging the magnetization lifetime by more than two years. The thickness dependence of the magnetic domain structure at room temperature indicated the preservation of magnetic domain stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been reported that a magnetic dead layer exists in magnetic oxides. ,, In addition, the interface is the region where secondary phases or precipitates can be easily formed . To identify the surface dead layer and to understand the mechanism of the magnetization in the interface, we employed polarized neutron reflectometry (PNR) to identify the magnetic profile of the sample …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that a magnetic dead layer exists in magnetic oxides. ,, In addition, the interface is the region where secondary phases or precipitates can be easily formed . To identify the surface dead layer and to understand the mechanism of the magnetization in the interface, we employed polarized neutron reflectometry (PNR) to identify the magnetic profile of the sample …”
Section: Resultsmentioning
confidence: 99%